Konstitusionalitas Perlindungan Hukum Terhadap Kebebasan Beragama dan Beribadah di Indonesia - Razak, Askari; A. Sakti R.S. Rakia; A. Darmawansya (Fakultas Hukum Universitas Muhammadiyah Sorong, 2022)
In the explanation of Law no. 1/PNPS/1965 stated that the recognized religions in Indonesia are Islam, Christianity, Catholicism, Hindu Buddhism, and Confucianism. As a result, other beliefs loses its legal standing and legal protection by the state. The issue of religious freedom is also influenced by the different interpretations of the terms